The Relationship of Motivation with The Level of Nurses' Compliance in Performing Hand Hygiene in The Surgical and Internal Partition Areas of Raden Mattaher Hospital Jambi - Adinda Putri Bestari Dinda; Indah Mawarni Ondag; Suryadi Imran (West Science Interdisciplinary Studies, 2024)
Hand hygiene is a program carried out by WHO to overcome HAIs. The implementation of this program is influenced by various things such as nurse motivation and compliance. Efforts to prevent HAIs that health workers can take are to increase their ability and motivation by implementing standard precautions, namely practicing hand hygiene. Motivation is needed by nurses to comply with the implementation of hand hygiene. This study aims to determine whether there is a relationship between motivation and nurses' compliance in carrying out hand hygiene. The design of this research is descriptive correlative with a cross sectional approach. The sample in this study was taken using a total sampling technique, namely 71 nurses. The variables studied were motivation and compliance in carrying out hand hygiene. Data collection was carried out by distributing questionnaires and observation sheets. Data were analyzed using Spearman Rank Correlation with significance α≤0.05. The research results showed that of the 71 respondents who had good motivation, 44 (83.0%) respondents complied with hand hygiene and 9 (17.0%) respondents did not comply with hand hygiene. Respondents with moderate motivation were 18 (100.0%) respondents who did not comply with hand hygiene. Meanwhile, there were no nurses found with less motivation. The results of the analysis of the relationship between motivation and the level of nurse compliance in carrying out hand hygiene showed that the p-value was 0.01. There is a relationship between motivation and nurse compliance in carrying out hand hygiene. Most nurses have good motivation and are obedient in carrying out hand hygiene. However, there are still nurses who have moderate motivation and are not compliant in carrying out hand hygiene. Therefore, further efforts need to be made to increase nurses' motivation and compliance in carrying out hand hygiene.